Peran Pembelajaran IPS Dalam Pembentukan Karakter Siswa SMP 35 Medan - Nurul Febriyani Harahap, Margaret Pangaribuan, Muhammad Hafiz Faisal, Tasya Marbun, Julia Ivanna (Ability: Journal of Education and Social Analysis, 2023)
Social studies learning is a learning process that focuses on Social Sciences. Social studies is a discipline that studies various aspects of social, political, economic and cultural life. This research aims to explore the role of Social Studies learning in students' character building at SMP 35 Medan. The research method used is descriptive qualitative method, which aims to gain an in-depth understanding of the role of social studies learning in shaping student character. In this study the data used is through interviews, observation, documentation and data analysis in the form of Data Reduction, Data Presentation, and Conclusion Drawing. The results of this study are social studies learning can help students develop critical attitudes, tolerance, cooperation, social responsibility, and critical thinking skills. Through an understanding of social, political, economic, and cultural issues, students can gain greater insight into the world around them.